2008
DOI: 10.1111/j.1572-0241.2007.01639.x
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Biopsy Diagnosis of Acute Gastrointestinal Graft-Versus-Host Disease: Rectosigmoid Biopsies Are More Sensitive Than Upper Gastrointestinal Biopsies

Abstract: Biopsy of the rectosigmoid is the single best test for diagnosing GI GVHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
70
5
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(89 citation statements)
references
References 38 publications
9
70
5
2
Order By: Relevance
“…However, another prospective study that included data from both upper and lower GIS biopsies reported that biopsies from the distal colon had the highest sensitivity for a diagnosis (17). These results were further confirmed by Ross et al (10) in 2008.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…However, another prospective study that included data from both upper and lower GIS biopsies reported that biopsies from the distal colon had the highest sensitivity for a diagnosis (17). These results were further confirmed by Ross et al (10) in 2008.…”
Section: Discussionsupporting
confidence: 76%
“…There is a lack of consensus regarding whether upper or lower GIS endoscopy is required first and which site has the highest sensitivity for biopsy (7,(9)(10)(11). It should be noted that thrombocytopenia often prevents invasive procedures in these patients, and clinicians generally worry about associated complications.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the segment of the gastrointestinal tract that should be biopsied for diagnosis of acute GI-GVHD remains subject to controversy. 25,26 Finally in our study, we did not expect a correlation between pathology scores and 18 F-FDG PET/CT, as 18 F-FDG PET/CT detects inflammation earlier before the onset of histological lesions, while the pathology score of GI-GVHD is based only on apoptosis and crypt loss 9 and does not take into account endothelial inflammation involved in GI-GVHD but detected by 18 F-FDG PET/CT, for example.…”
Section: Discussionmentioning
confidence: 97%
“…Their study analyzed 112 patients who underwent simultaneous endoscopic biopsies of the stomach, duodenum and recto-Open Journal of Internal Medicine sigmoid colon within the first 100 days after allo-SCT. Rectosigmoid biopsies showed the highest sensitivity (95.6%) and specificity (100%) [15]. Kreisel et al found that in about 20% of patients with ileo-colonoscopy, typical GVHD lesions could be found only in the terminal ileum [9].…”
Section: Discussionmentioning
confidence: 99%